Report on the Conference for the 100th Anniversary of Choi Hong Hi: Taekwon-Do and Life; How to View Choi Hong Hi (Revista de Artes Marciales Asiáticas, 2018)
General Choi Hong Hi has long been a controversial figure in the Republic of Korea (ROK; South Korea) despite his extreme influence on Taekwondo. The “Conference for the 100th Anniversary of Choi Hong Hi: Taekwon-Do and Life; How to View Choi Hong Hi” was held on November 28, 2018 at the Korea National Sport University. This report on that conference intends to disseminate the speakers’ findings to a wider audience and establish new directions for academic discussions on International Taekwon-Do Federation (ITF) Taekwon-Do. This conference also illuminated some problems with Taekwondo literature; namely that ITF literature is greatly overshadowed by research on its Olympic counterpart. Additionally, it seems that the only ROK Taekwondo governing body interested in reestablishing General Choi’s legacy is the Taekwondo Promotion Foundation. Nevertheless, even though he was a taboo topic in the ROK a decade ago, the political climate in the ROK has changed and General Choi’s legacy is re-emerging slowly.